2016
DOI: 10.1111/1755-6724.13014
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian Reefs in the Western North China Platform, Wuhai, Inner Mongolia

Abstract: Mid to late Cambrian thrombolites and maze‐like maceriate reefs from the western North China Platform, Wuhai, Inner Mongolia, northwestern China, occur in the middle of a succession dominated by thin‐bedded lime mudstone‐shale/marlstone alternations, and are laterally surrounded by limestone conglomerate and/or grainstone. Thrombolite, characterized by meter‐scale lenticular mounds composed of millimeter‐ to centimeter‐scale mesoclots and wackestone matrix, occurs in the lower middle part of the sequence. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…14; Khanna et al ., 2020a; Lehrmann et al ., 2020). These distinctive and well‐preserved fabrics shed light on the origins of structures of similar age and appearance that are widely distributed around North America (Shapiro & Awramik, 2006, and references therein) and are also well‐known in Argentina (Armella, 1994; Raviolo et al ., 2010) and China (Lee et al ., 2010, 2014, 2016; Chen et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14; Khanna et al ., 2020a; Lehrmann et al ., 2020). These distinctive and well‐preserved fabrics shed light on the origins of structures of similar age and appearance that are widely distributed around North America (Shapiro & Awramik, 2006, and references therein) and are also well‐known in Argentina (Armella, 1994; Raviolo et al ., 2010) and China (Lee et al ., 2010, 2014, 2016; Chen et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…4e) noted upper Cambrian ‘mazelike structures’ in column interiors in Utah. Favosamaceria has also been described from Argentina (Raviolo et al ., 2010), and similar fabrics have been described from various localities in North China (Lee et al ., 2010, 2014, 2016) where Chen et al . (2014, p. 250) noted that “The deposition rate of inter‐macerial sediment was most likely balanced with the growth rate of maceriae, sustaining a low synoptic relief”.…”
Section: Discussionmentioning
confidence: 99%
“…Myrow et al (2015) focused on the upper part of this succession, consisting of fine-grained sedimentary facies such as lime mudstone and marlstone alternations, and they reported that trilobites belonging to the Black welderia zone, indicating the middle Guzhangian Stage of Cambrian Series 3 (Park et al, 2013), occur 18.51 m below the Cambrian-Ordo vician boundary. Lee et al (2016) reported trilobite Jiulongshania rotundata from strata 16.4 m below the boundary, which also occurs within the Blackwelderia zone of Myrow et al (2015). Sedimentary facies as well as trilobite occurrences collectively suggest a relatively slow sedimentation rate, indicating that the uppermost part of the Cambrian succession in Wuhai area would not exceed the Guzhangian Stage (Myrow et al, 2015;Lee et al, 2016).…”
Section: Cambrian-ordovician Unconformities On the Sino-korean Blockmentioning
confidence: 98%
“…At the Subaiyingou (or Subeigou) section where the study was conducted, the Cambrian-Ordovician boundary occurs ~360 m above the Precambrian-Cambrian unconformity (Lee et al, 2016). Myrow et al (2015) focused on the upper part of this succession, consisting of fine-grained sedimentary facies such as lime mudstone and marlstone alternations, and they reported that trilobites belonging to the Black welderia zone, indicating the middle Guzhangian Stage of Cambrian Series 3 (Park et al, 2013), occur 18.51 m below the Cambrian-Ordo vician boundary.…”
Section: Cambrian-ordovician Unconformities On the Sino-korean Blockmentioning
confidence: 99%
See 1 more Smart Citation